The effect of spicy food on bonding and bias - Lim, Dionis Si Ying (2017)
Eating spicy food is typically an experience of pain. Research has shown that shared experiences of pain can promote bonding and cooperation. Humans are inherently social and have a need to affiliate, and fulfil this social need by prioritizing affiliation and the welfare of one’s ingroup. Therefore, this study seeks to examine if eating a common type of spicy food, which elicits pain, with one’s group increases bonding (H1) and intergroup bias (H2). It is hypothesised that eating spicy food with one’s group would increase one’s feelings of bonding with group members, as well as a favouritism for one’s ingroup. Participants (n = 84) were undergraduates from Nanyang Technological University who either consumed spicy or non-spicy versions of the same food as their ingroups before completing measures of bonding, as well as evaluative and behavioural intergroup bias, which would reflect ingroup favouritism. Results from this study partially supported the first hypothesis, whereas the second hypothesis was not supported. These findings and their implications, along with the limitations and future directions of the current research, are discussed in the paper.